2023
DOI: 10.3390/ma16031303
|View full text |Cite
|
Sign up to set email alerts
|

Recent Trends in Hydroxyapatite Supplementation for Osteoregenerative Purposes

Abstract: Bone regeneration has gained attention in the biomedical field, which has led to the development of materials and synthesis methods meant to improve osseointegration and cellular bone activity. The properties of hydroxyapatite, a type of calcium phosphate, have been researched to determine its advantages for bone tissue engineering, particularly its biocompatibility and ability to interact with bone cells. Recently, the advantages of utilizing nanomolecules of hydroxyapatite, combined with various substances, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 205 publications
0
4
0
Order By: Relevance
“…This seems to be in agreement with reports by Hou et al [ 3 ] and Marques Loureiro et al [ 5 ], who observed that chronic intake of an unbalanced high-fat diet can contribute to disorders in bone modelling and remodelling by increasing the risk of deficiencies of important nutrients involved in bone metabolism, such as calcium, phosphorus, and vitamin D 3 . Ca and P are essential tohydroxyapatite synthesis andbone mineralization, ensuring adequate bone strength [ 37 ]. Sufficient amounts of calcium and phosphates fornormal mineralizationcan be ensured by the active form ofvitamin D 3 ,regarded as a factor activating osteoclast maturation processes by increasing the expression of RANKL and reducing OPG levels [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…This seems to be in agreement with reports by Hou et al [ 3 ] and Marques Loureiro et al [ 5 ], who observed that chronic intake of an unbalanced high-fat diet can contribute to disorders in bone modelling and remodelling by increasing the risk of deficiencies of important nutrients involved in bone metabolism, such as calcium, phosphorus, and vitamin D 3 . Ca and P are essential tohydroxyapatite synthesis andbone mineralization, ensuring adequate bone strength [ 37 ]. Sufficient amounts of calcium and phosphates fornormal mineralizationcan be ensured by the active form ofvitamin D 3 ,regarded as a factor activating osteoclast maturation processes by increasing the expression of RANKL and reducing OPG levels [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…This potential advancement could lead to toothpastes tailored to various levels of enamel damage and sensitivity. Another approach could be to develop hydroxyapatite nanoparticles that accurately transport active compounds, such as antimicrobial or anti-inflammatory molecules [29]. These nanoparticles might be engineered to gradually release beneficial bio-compounds over time.…”
Section: Discussionmentioning
confidence: 99%
“…Hydroxyapatite is used as such in toothpastes [25][26][27] and bone regeneration [28,29], or as substituted in its lattice with various physiological elements to enhance its bioactivity, like Zn [30], Zn-carbonate [31], Sr [32,33], Zn and Sr [34], Cu and Zn [35], Zn and fluoride [36], fluorine [37], Ag and fluoride [38], Mg and Sr [39], Mg [40], Mg and Zn [41], Mg and Si [42], Ag [43], and Si [44]. These components play various roles; for some, the particular role they play in the substituted HAP is known; for others, it is only assumed.…”
Section: Introductionmentioning
confidence: 99%
“…Recent trends towards strontium substituting calcium in hydroxyapatite have resulted in increased crystallinity and bioactivity [17]. Strontium exhibits osteoinduction and high solubility.…”
Section: Introductionmentioning
confidence: 99%